2010
DOI: 10.1186/1478-4491-8-27
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and motivation of health workers in public and private sectors: cross-sectional analysis from two Indian states

Abstract: BackgroundEnsuring health worker job satisfaction and motivation are important if health workers are to be retained and effectively deliver health services in many developing countries, whether they work in the public or private sector. The objectives of the paper are to identify important aspects of health worker satisfaction and motivation in two Indian states working in public and private sectors.MethodsCross-sectional surveys of 1916 public and private sector health workers in Andhra Pradesh and Uttar Prad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
142
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(160 citation statements)
references
References 28 publications
14
142
0
4
Order By: Relevance
“…This study revealed factors such as opportunity for training, relation among with colleagues, working environment, basic medical equipment and supplies as motivating factors this is also true with study done in Indian two state [ 35]. This is due to Herzberg theory of motivation; the theory consider the mentioned factors as hygienic (extrinsic) factors which affects motivation so this both study is in line with the theories of two factors of Herzberg.…”
Section: Discusionsupporting
confidence: 71%
“…This study revealed factors such as opportunity for training, relation among with colleagues, working environment, basic medical equipment and supplies as motivating factors this is also true with study done in Indian two state [ 35]. This is due to Herzberg theory of motivation; the theory consider the mentioned factors as hygienic (extrinsic) factors which affects motivation so this both study is in line with the theories of two factors of Herzberg.…”
Section: Discusionsupporting
confidence: 71%
“…These 44 items were chosen based on previous studies and a panel discussion that examined desired and perceived workplace incentives for health workers [10,17,18]. There were two aspects to each incentive item: desirability and perception.…”
Section: Methodsmentioning
confidence: 99%
“…Although this result is somewhat surprising, it is not entirely unexpected. Both qualitative and quantitative data have shown that although health workers may not be satisfied with their remuneration, this is not the primary cause of their job satisfaction or dissatisfaction [33,75,124] as seems to be the case of health workers in BĂ©nin. Chu et al's 2003 study among Taiwanese nurses of the causal model of job satisfaction determined that variables such as involvement, workload and resource inadequacy, social support, and promotion were all significantly related to job satisfaction --except for pay; exogenous variables of health clinics explained 45% of the variance in job satisfaction [74].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, there are a multitude of different definitions for job satisfaction and it is difficult to select among them. Most researchers, however, agree that satisfaction is an attitudinal variable representing the overall assessment of one's job as experienced in the workplace [33][34][35][36]. Other researchers describe it as a pleasurable emotional state that a person feels towards his or her job.…”
Section: Defining Job Satisfactionmentioning
confidence: 99%